IMPLEMENTASI PERATURAN WALIKOTA NOMOR 27 TAHUN 2020 TENTANG ADAPTASI KEBIASAAN BARU MENUJU MASYARAKAT PRODUKTIF DAN AMAN PADA SITUASI CORONA VIRUS DISEASE 2019 (COVID-19) DI KELURAHAN SUNGAI SELINCAH KECAMATAN KALIDONI PALEMBANG (STUDI KASUS PASAL 3) - Supardi, Supardi; Daliyah, Dhea (STIA SATYA NEGARA PALEMBANG, 2023)
The purpose of this study was to analyze the implementation of Mayor Regulation No. 27 of 2020 concerning Adaptation of New Habits Towards a Productive and Safe Society in the Corona Virus Disease 2019 (Covid-19) Situation in Sungai Selincah Village, Kalidoni District, Palembang. The implementation of the New Habit Adaptation is an implementation after the reduction of the Covid-19 pandemic and is called the New Normal condition for a more productive and safe community condition. Sungai Selincah Village is certainly inseparable from the problem of the Covid-19 pandemic, which until now has not yet been transitioned to a normal period. These problems have an impact on the implementation of the Adaptation of New Habits, the elements of which are still not obedient and disciplined or have not made it a habit to maintain personal health, and the socialization and participation of the government is also lacking in the conditions of new adaptation to the community. The research method that the author uses is a qualitative method, which means a study that aims to provide a more detailed and clear description of the state of the object. Data collection techniques were carried out by observation, interviews, documentation and literature study. Data analysis was carried out by means of data reduction, data presentation and drawing conclusions. The results of the study show that the implementation of Mayor Regulation Number 27 of 2020 concerning Adaptation of New Habits Towards a Productive and Safe Society in the Corona Virus Disease 2019 (COVID-19) Situation at the Sungai Selincah Village Office, Kalidoni Subdistrict, Palembang has been carried out quite well in accordance with existing policies. This is based on indicators of IMR implementation, residents' rights and obligations in implementing IMR, resources for handling COVID-19, coaching, monitoring, evaluation and reporting, socialization and participation, funding and sanctions.Key words :Implementation and Implementation of New Habit Adaptations